Simulation and hardware design of synthetic stereo circuit - Ramli, Yusrizal (2002)
This paper is a study of today's available home entertainment sound system which uses the concept of stereo sound production. However, most of sound productions are made with the basic of monaural signal. This paper will provides a complete understanding of stereo signal production converted from the monaural signal using electronic circuitry. The circuit will be designed, simulated and transferred to a hardware form and the result will be investigated.